(untitled) (Journal of Atomic and Molecular Sciences, 2011)
A kind of hybrid material was made through sol-gel process with the PMMA, TEOS, and 4-[N]-ethyl-N-(2-hydroxyethyl) amino-4'-nitro-azobenzene (DR1). And the films of sol were prepared by using the spin-coated method. Through all optical poling, it could be found that there exists an optimum thickness for film. In addition, the higher of sample temperature was, the smaller intensity of SHG was. The experiment showed that the SiO_2 network was existent, and hybrid materials significantly improved orientation stability.